Setting up a transgender-friendly service in a tertiary care hospital: The challenges and solutions - Manoj K. Sahoo; Chandrima Naskar; Vinita Singh; Akash Panigrahi (Indian Journal of Psychiatry)
Transgender and gender diverse (TGD) individuals face significant barriers to healthcare, necessitating the development of TGD-friendly medical services. In India, healthcare systems have only recently begun addressing the unique needs of TGD individuals, particularly with the advent of the Transgender Persons Act 2019. This article outlines the establishment of a comprehensive TGD clinic within a multidisciplinary framework. Services span psychiatric support, endocrinology, and surgical interventions, including gender-affirming medical and surgical treatments (GAMSTs). Adherence to WPATH Standards of Care (SOC-8) ensures informed, patient-centered treatment for gender incongruence. The clinic also emphasizes pretreatment evaluations, hormone therapy protocols, surgical readiness, and regular monitoring. Additionally, patient education, consent processes, and social transition support are integral to the clinic’s approach. Challenges include stigma reduction, staff training, financial sustainability for long-term treatments, and navigating gendered hospital infrastructure. The clinic’s experience with 50 TGD individuals, including 18 who underwent gender reassignment surgeries, demonstrates the feasibility of such a service. Future goals include expanding services to nonemployees, providing advanced surgeries, and enhancing mental health support. This model serves as a framework for the creation of inclusive, holistic healthcare services for TGD individuals in India, aiming to improve both physical and psychological wellbeing.